A heritage of freedom: monuments and the American legacy in the Philippine memoryscape, 1898-1978 - Weir, Kimberley Lustina (2022)
Using a combination of archival, material, spatial and art historical analysis, this thesis examines four monuments constructed or initiated during the colonial rule of the Philippines by the United States (1898 to 1946): the Rizal Monument (1913), the Bonifacio Monument (1933), the Quezon Memorial (1978) and the Pacific War Memorial (1968). I argue that while each of the monuments was used to project an image of the Philippine nation that was shaped by the country’s experience of US rule, this was complicated by alternative visions of nationhood articulated by other commemorative groups, including the Philippine government, veterans groups, the Knights of Rizal, artists, architects, as well as community and business leaders. This commemorative pluralism resulted in “polyphonic memoryscapes” around each of the monuments in which competing images of the nation, in part shaped by class, race and religious divides, exist and collide. These multiple networks of memory contest previous scholarship of the US-colonial Philippines, which has focused on the coloniser-colonised dichotomy, revealing that while tensions remained between the legacy of US rule and the assertion of an independent Philippine nationhood, Philippine monument building did not simply take place within a colonial or postcolonial context but connected to a number of global commemorative practices that positioned Philippine nationhood within a transnational nexus of heritages. In particular, the Bonifacio Monument and the Quezon Memorial were each shaped by broader post-revolution and postcolonial memoryscapes, revealing Philippine connections to the Hispanic diaspora, as well as the Soviet Union and the People’s Republic of China. This thesis also reveals the Christianised image of the nation that proliferates across Philippine colonial and postcolonial commemoration, belying the country’s religious diversity. It also demonstrates the significance of the body and reinterment to this Christian portrayal of the nation and the creation of a sanctified memorial space. Finally, I assert that while the United States used commemoration to depict Philippine independence as a consequence of the US ideal of “freedom”, for Philippine commemorative agents, Philippine nationhood was always founded on the country’s own “heritage of freedom”.